Pengembangan Bahan Ajar Berbasis Learning Cycle untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII SMP Kabupaten Tapanuli Utara - Belman Mangapul R Horbo (LP. Ma'arif Janggan Magetan, 2023)
This study describes the development of learning cycle teaching materials that are valid, effective, and practical for improving students' mathematics learning outcomes in class VIII SMP Tapanuli Utara and improving student mathematics learning outcomes using teaching materials based on the learning cycle method developed in class VIII SMP Tapanuli District North. As subjects in this study were class VIII students of SMP Negeri 2 Parmonangan for the 2021/2022 Academic Year. As subjects in this study were class VIII students of SMP Negeri 2 Parmonangan for the 2021/2022 Academic Year. The object of this research is mathematics teaching materials which are developed based on the learning cycle learning method to improve mathematics learning outcomes in the Pythagorean Theorem material. The research model is development research with a modification of the Borg and Gall development procedure. Development research is generally divided into 3 (three) stages, namely the problem identification stage, the design stage, and the deployment stage. The results of the study stated that the teaching materials based on the learning cycle method developed were valid, effective, and practical to use to improve students' mathematics learning outcomes in class VIII of SMP Tapanuli Utara. Teaching materials based on the learning cycle method developed can improve student learning outcomes in class VIII of SMP Tapanuli Utara. Obtaining arithmetic results or an N-Gain value of 0.64 with the category of moderate or good learning improvement results.